Biodegradation of 1080: Testing soils in south‐eastern Australia for sodium fluoroacetate‐degrading micro‐organisms. (7th November 2013) - Gentle, Matthew; Cother, Eric
Summary Sodium fluoroacetate (1080) is a vertebrate poison commonly used for the control of vertebrate pests in Australia. Long‐term environmental persistence of 1080 from baiting operations has likely nontarget species and environmental impacts and is a matter of public concern. Defluorinating micro‐organisms have been detected in soils of Western and central Australia, and Queensland, but not in south‐eastern Australia. The presence or absence of defluorinating micro‐organisms in soils from south‐eastern Australia will assist in determining whether long‐term environmental persistence of 1080 is or is not occurring. Soils from the Central West Slopes and Plains and Central Tablelands of New South Wales were sampled to investigate the presence and capability of 1080 defluorinating soil micro‐organisms. Thirty‐one species of micro‐organisms were isolated from soils from each site after 10 days incubation in a 20 mM 1080 solution. Of these, 13 isolates showed measurable defluorinating ability when grown in a 1080 and sterile soil suspension. Two species, the bacteria Micromonospora, and the actinomycete Streptosporangium, have not been previously reported for their defluorinating ability. These results indicate that defluorinating micro‐organisms are present in soils in south‐eastern Australia, which adds weight to other studies that found that 1080 is subject to microbiological degradative processes following removal from the bait substrate. Soil micro‐organism defluorination, in combination with physical breakdown and uptake by plants, indicates that fluoroacetate in soils and natural water ways is unlikely to persist. This has implications for the better informed use of 1080 in pest animal management programmes in south‐eastern Australia.